An Advanced High‐Entropy Fluorophosphate Cathode for Sodium‐Ion Batteries with Increased Working Voltage and Energy Density. Issue 14 (25th February 2022) - Gu, Zhen‐Yi; Guo, Jin‐Zhi; Cao, Jun‐Ming; Wang, Xiao‐Tong; Zhao, Xin‐Xin; Zheng, Xue‐Ying; Li, Wen‐Hao; Sun, Zhong‐Hui; Liang, Hao‐Jie; Wu, Xing‐Long
Abstract: Impossible voltage plateau regulation for the cathode materials with fixed active elemental center is a pressing issue hindering the development of Na‐superionic‐conductor (NASICON)‐type Na3 V2 (PO4 )2 F3 (NVPF) cathodes in sodium‐ion batteries (SIBs). Herein, a high‐entropy substitution strategy, to alter the detailed crystal structure of NVPF without changing the central active V atom, is pioneeringly utilized, achieving simultaneous electronic conductivity enhancement and diffusion barrier reduction for Na +, according to theoretical calculations. The as‐prepared carbon‐free high‐entropy Na3 V1.9 (Ca, Mg, Al, Cr, Mn)0.1 (PO4 )2 F3 (HE‐NVPF) cathode can deliver higher mean voltage of 3.81 V and more advantageous energy density up to 445.5 Wh kg −1, which is attributed by the diverse transition‐metal elemental substitution in high‐entropy crystalline. More importantly, high‐entropy introduction can help realize disordered rearrangement of Na + at Na(2) active sites, thereby to refrain from unfavorable discharging behaviors at low‐voltage region, further lifting up the mean working voltage to realize a full Na‐ion storage at the high voltage plateau. Coupling with a hard carbon (HC) anode, HE‐NVPF//HC SIB full cells can deliver high specific energy density of 326.8 Wh kg −1 at 5 C with the power density of 2178.9 W kg −1 . This route means the unlikely potential regulation in NASICON‐type crystal with unchangeable active center becomes possible, inspiring new ideas on elevating the mean working voltage for SIB cathodes. Abstract : A high‐entropy effect is delicately introduced into fluorophosphate cathode for sodium‐ion batteries by in situ partial substitution of active V central atom, preparing a high‐entropy carbon‐free Na3 V1.9 (Ca, Mg, Al, Cr, Mn)0.1 (PO4 )2 F3 cathode, suppressing the occurrence of detrimental phase transition process in the low‐voltage region, and further lifting up the mean working voltage of pristine Na3 V2 (PO4 )2 F3, enhancing sodium storage behavior, rate capability, and cycle performance.